INFLUENCE OF OXAMINE ACID DERIVATIVES ON THE SECRETORY FUNCTION OF KIDNEYS - Litvinova, O.N.; Litvinov, V.S. (World of Medicine and Biology, 2018)
The purpose of this project was to experimentally study the effect of new dicarboxylic acids derivatives on the excretory function of the kidneys. The studied compounds under the water loading conditions have a multidirectional effect on the kidneys excretory function in white rats of the Wistar line. The diuretic activity of the studied compounds was influenced both by the chemical structure of the substances and by its location. As a result of the performed research, substances increasing diuresis with the diuretic activity exceeding that of the reference preparation – hypothiazide – were found. Among the studied compounds, there were substances with an antidiuretic effect. Replaced arensulfoniloxamine acid amides are the perspective group of compounds for further pharmacological study with the aim of development of new medicines with diuretic activity on their basis.
Keywords: dicarboxylic acids derivatives; oxamine acid derivatives; excretory function of the kidneys; diuretic activity; antidiuretic effect